SYMPTOM BURDEN AMONG OLDER ADULTS WITH NON-HODGKIN LYMPHOMA UNDERGOING CHEMOTHERAPY IN SOME HOSPITAL OF HANOI (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the prevalence and severity of symptoms among older adults with non-Hodgkin lymphoma undergoing chemotherapy at oncology hospitals in Hanoi.Methods: A cross-sectional study was conducted on 139 older patients diagnosed with non-Hodgkin lymphoma at oncology hospitals in Hanoi.Results: The sample consisted of 77 males (55.4%) and 62 females (44.6%), with a mean age of 68.1 ± 5.3 years. The most commonly reported symptoms included hair loss (77.7%), numbness/tingling in hands or feet (67.6%), dry mouth (59.7%), difficulty sleeping (62.6%), lack of appetite (52.5%), change in the way food tastes (50.4%), lack of energy (44.4%), shortness of breath (42.4%), weight loss (43.9%), and worrying (41.7%). Hair loss was the most severe symptom (mode = 3), while symptoms like numbness in extremities, dry mouth, appetite loss, taste changes, insomnia, shortness of breath, fatigue, and anxiety (mode = 2). Less frequent symptoms such as diarrhea, nausea, and sweats were mild (mode = 1). Some symptoms as mouth sores, feeling sad, and headache had a mode of 2 but a median of 1, indicating skewed perception of severity. Conclusions: Older adults with non-Hodgkin lymphoma undergoing chemotherapy commonly experience multiple symptoms, notably hair loss, numbness/tingling in hands or feet, dry mouth, and difficulty sleeping. In terms of severity, most symptoms were rated as mild to moderate by patients, with only hair loss identified as severe (mode = 3). These findings reflect the complexity and diversity of symptom experiences among older adults with non-Hodgkin lymphoma receiving chemotherapy. The results underscore the need for healthcare professionals-particularly physicians and oncology nurses-to develop tailored symptom management and patient education materials to improve care quality and treatment outcomes for this vulnerable population.
Keywords: Non‑Hodgkin lymphoma, elderly, symptoms, MSAS.